The Level of Artificial Intelligence Use and Its Relationship with Self-Directed Learning among Gifted Students - حسن, آ.م.د. ئاڤان عبدالله حسن; امین, م.م. نیهایەت فرج محمد امین (Sulaimani Journal for Humanities, 2025)
The present research aimed to identify the level of artificial intelligence (AI) use and the level of self-directed learning among gifted students, as well as to determine the relationship between these two variables. It also sought to examine statistical differences in the level of self-directed learning according to gender and to explore the relationship between AI use and self-directed learning. The researchers employed the descriptive correlational method. To achieve the objectives of the study, two instruments were developed by the researchers: the Artificial Intelligence Use Scale and the Self-Directed Learning Scale. After verifying the psychometric properties of both scales, they were administered to a sample of 103 male and female students from Azmar College for the Gifted in the city of Sulaimani. The data were analyzed using the One-Sample T-test, Independent Samples T-test, Kolmogorov-Smirnov test, Cronbach’s Alpha coefficient, and Regression Analysis. The findings revealed that the levels of artificial intelligence use and self-directed learning among gifted students were high. Moreover, a moderate, positive, and direct correlation was found between AI use and self-directed learning. No statistically significant differences were observed in AI use based on gender. In light of these findings, the researchers proposed a set of recommendations and suggestions.
Keywords: Artificial Intelligence; Self Directed Learning; Gifted Students